ANALISIS EFISIENSI ALOKATIF USAHATANI CABAI MERAH BESAR DI DESA SUKALAKSANA KECAMATAN BANYURESMI KABUPATEN GARUT - Tina Sonia; Tuti Karyani; Agus Susanto (Universitas Galuh Ciamis, 2020)
Most of farmers in Sukalaksana Village Banyuresmi District are red chili farmers, but their red chili production has not been optimal so that the productivity of red chili in Sukalaksana is the lowest compared to other village. Production is influenced by production factors, the right combination of production factors is needed to produce optimal and economically efficient production. The purpose of this study is to identify the factors that influence production and analyze allocative efficiency of production factors in red chili farming in Sukalaksana Village. The research method used was a survey method with analytical techniques using the Cobb Douglas production function model. The results showed that labor, seeds, manure, NPK fertilizer, and pesticides simultaneously influenced the production of red chili in Sukalaksana Village with 85.3 percent determination coefficient. Production factors that partially have a significant effect on red chili production in Sukalaksana Village are labor, seeds, and NPK fertilizer. Based on allocative efficiency analysis, labor and seeds has not been efficient so its needs to be added, NPK fertilizer is not efficient so its needs to be reduced.